Outcome of Percutaneous Nephrolithotomy in Patients with History of Open Renal Stone Surgery (Bangladesh Journal of Urology, 2022)
Background: Percutaneous nephrolithotomy (PCNL) in patients operated previously for renal stone are thought to pose some difficulties.Objective: To see the outcome of PCNL in patients who had undergone open surgery for renal stone.Method: This cross sectional study was conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University, Dhaka from November 2015 to October 2016 over a period of one year. Thirty cases with recurrent stone having previous open renal stone surgery were enrolled as study subject. After PCNL all the patients were followed up at one week, one month and three months after procedure.Result: Mean age of the patients was 40.90 ± 6.08 years and mean stone size was 2.98 ± 0.65 cm. Mean operation time of the patients was 1.50 ± 0.46 hours and mean postoperative hospital stay was 3.87 ± 1.13 days. Stone was cleared from 29 (96.7%) patients. Mean drop of Haemoglobin level was 0.85 ± 0.55 mg/dl.Conclusion: Previous open stone surgery does not alter the outcome of subsequent PCNL.Bangladesh J. Urol. 2021; 24(1): 58-61